The methodic of choosing the algorithm of planning the experiment for making the research of aircraft surface damage influence the aircraft’s controllability - Казак, В. М. (Proceedings of National Aviation University (archive), 2021)
The problem of planning the optimal experiment under the conditions of getting the maximum information about the mechanism of influence the aircraft surface damage the aircraft’s flight characteristics under the limited expenses is considered. The criterions of choosing the optimal experiment are defined.